2014
DOI: 10.1111/hcre.12022
|View full text |Cite
|
Sign up to set email alerts
|

Humiliate My Enemies or Mock My Friends? Applying Disposition Theory of Humor to the Study of Political Parody Appreciation and Attitudes Toward Candidates

Abstract: The research examines politically entertaining media through a mass communication lens, applying the disposition theory of humor toward the study of political parody appreciation and the effects of exposure to varied humor types on political attitudes. The analyses rely on experimental data (N = 269) collected in 2013. The results of the first analysis suggest that the interaction of disposition and exposure to different types of humor significantly influences variation in political parody appreciation. The fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 65 publications
1
38
1
Order By: Relevance
“…The current study has shown that if background information was provided, it affected the appreciation of satire; thereby, it provides evidence for both selective processing mechanisms (LaMarre et al, ; Vidmar & Rokeach, ) and disposition theory (Becker, ; Zillmann & Cantor, ). Indicative of selective processing was that people without background knowledge found the satire equally funny.…”
Section: Discussionsupporting
confidence: 54%
“…The current study has shown that if background information was provided, it affected the appreciation of satire; thereby, it provides evidence for both selective processing mechanisms (LaMarre et al, ; Vidmar & Rokeach, ) and disposition theory (Becker, ; Zillmann & Cantor, ). Indicative of selective processing was that people without background knowledge found the satire equally funny.…”
Section: Discussionsupporting
confidence: 54%
“…Related research applying the disposition theory of humor to political contexts has shown that individuals exhibit greater appreciation for humor that pokes fun at a candidate or politician they dislike but are less receptive PARODY, ANXIETY REDUCTION, AND POLITICAL EFFICACY toward humor that mocks an affiliate (Zillmann, Bryant, & Cantor, 1974;Zillmann, Taylor, & Lewis, 1998). In fact, recent work has suggested that disposition can moderate the impact of exposure to attack humor on related political attitudes, resulting in less favorable evaluations of the candidate being mocked given a prior negative orientation toward the attacker (Becker, 2014). Extending this dynamic to the current case study, it should follow that a preference for humor that attacks the opposition should reinforce or be positively related to evaluations of efficacy, whereas humor that attacks an affiliate or a candidate that one likes should reduce judgments of one's ability to effectively understand and participate in the political process.…”
Section: Affinity For Political Humor Anxiety Reduction Humor Orienmentioning
confidence: 99%
“…Of course this may depend both upon the prior partisan leanings of the individual and the type of humor to which they are exposed (Becker, 2014). For example, seeing the opposing candidate being mocked should lead to more positive feelings of internal political efficacy, particularly among individuals with high levels of affinity toward political humor as an anxiety reduction tool.…”
Section: Afph-anxiety and Moderationmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, too, much of the work is experimental, using college students (or college‐aged individuals) as subjects. The consensus from most of this research is that humor has a message‐consistent effect on opinions of its target (Baumgartner, ; Baumgartner and Morris, , , ; Baumgartner, Morris, and Walth, ; Becker, ; Esralew and Young, ; Morris, ; Nabi, Moyer‐Gusé, and Byrne, ). For example, humor that ridicules a particular individual (e.g., a president or presidential candidate) will lower opinions of that individual.…”
Section: Political Humor Viewership Effects Scholarshipmentioning
confidence: 99%